Linking Learning Contexts: The Relationship between Students’ Civic and Political Experiences and Their Self-Regulation in School - Malafaia, Carla; Teixeira, Pedro M.; Neves, Tiago; Menezes, Isabel (Frontiers in Psychology, 2016)
This paper considers the relationship between self-regulation strategies and youth civic and political experiences, assuming that out-of-school learning can foster metacognition. The study is based on a sample of 732 Portuguese students from grades 8 and 11. Results show that the quality of civic and political participation experiences, together with academic self-efficacy, are significant predictors of young people’s self-regulation, particularly regarding cognitive and metacognitive strategies (elaboration and critical thinking). Such effects surpass even the weight of family cultural and school variables, such as the sense of school belonging. Therefore, we argue that the pedagogical value of non-formal civic and political experiences is related to learning in formal pedagogical contexts. This is because civic and political participation with high developmental quality can stimulate higher-order cognitive engagement and, thus, contribute to the development of learning strategies that promote academic success.